Women mentoring women : Contradictions, complexities and tensions - Joyce Stalker (Adult Education Research Conference, 1996)
Women who mentor women enter into a complex adult learner/teacher relationship filled with contradictions and tensions. Normally it is viewed as having positive implications for both the learner and the teacher. In an earlier paper (Stalker, 1994) I theorised, from a feminist perspective, this phenomenon. The purpose of this paper is to explore that theorisation through the empirical study of women mentoring women in the academy. The paper first presents briefly a feminist critique of the traditional conceptualisation of mentoring. It then focuses on the theoretical implications of that critique which formed the basis for the empirical study. The methodology and selected findings are followed by a brief discussion of the findings and their relevance to our understandings of women mentoring women in the academy.